THE INFLUENCE OF MOBILE MARKETING ON CONSUMER ATTITUDE STUDY AT STUDENT OF SAM RATULANGI UNIVERSITY - Nicolaas, Gisyela P.Z. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Advances in Information and Communication Technology not only offers new marketing channels of communication and interactivity to the company but also significantly affect the way companies conduct their business and marketing activities.Marketing on Mobile devices has become one of the most popular channels of communicating with intending and potential customers, particularly in the form of text advertising through Instant Messaging Service. The study aims to determine the effect of mobile marketing on consumer attitudes among mobile phone users in Sam Ratulangi University students and to examine the influence of entertainment, information and credibility on consumer attitudes to marketing via the mobile. Data collection method of this is using a questionnaire. Multiple regression analysis was used to test the stated hypothesis and to find out the influence of dependent variable with independent variables. The Result of this research found that entertainment and credibility has a significant influence to the consumer attitude by using mobile marketing (except for information). The study recommends that: For companies who use this marketing strategy to send a message via the mobile need to better understand the demographic characteristics of consumers in order to develop marketing programs via cellular. Keywords : mobile marketing, entertainment, informativeness, credibility, consumer attitude